FINE ARTS EDUCATION BASED ON A COMPETENCY-ORIENTED APPROACH GROUNDED IN COLOR PSYCHOLOGY - Aminov Akmal Shavkatovich; Amrullayeva Oysha Azamat qizi (American Journals, 2026)
This article analyzes the theoretical and practical aspects of a competency-oriented approach based on color psychology in fine arts education. The study explores the possibilities of developing students’ creative, aesthetic, and communicative competencies through the psychological impact of colors. The results of pedagogical experimental work demonstrate that the conscious and purposeful use of colors significantly enhances students’ motivation for artistic activity, emotional state, and creative thinking. The findings substantiate the importance of implementing a competency-based model grounded in color psychology in the modernization of fine arts education.
Keywords: Color psychology, competency-based approach, fine arts education, creative competence, aesthetic education, pedagogical technologies.